Menginvestigasi Perilaku Pembelian Impulsif pada Platform E-Commerce dalam Fenomena Doom Spending Generasi Z - Rizky Andrean; Muhammad Khoirul Fikri; Azzah Liddiana; Eka Mega Pertiwi; Elis Ratna Wulan (At-Taradhi Jurnal Studi Ekonomi, 2025)
The development of digital technology and the rapid use of e-commerce platforms have driven changes in consumption behavior, especially among Generation Z. One of the emerging phenomena is doom spending, which is spending carried out in response to emotional pressure or stress. This study aims to examine the effect of hedonic shopping motivation, social influence, and perceived ease of use of e-commerce platforms on impulsive buying among Generation Z in the Pekalongan. This study uses quantitative method, with a purposive sampling technique of 269 respondents. Data analysis was carried out by SEM-PLS analysis using SEM-PLS 3. The results of this study showed that hedonic shopping motivation and social influence had a positive and significant effect on impulsive buying, while perceived ease of use had no significant effect on impulsive buying